2005
DOI: 10.1098/rspb.2005.3194
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive sex differences in growth of pre-ovulation oocytes in a passerine bird

Abstract: Maternal modification of offspring sex in birds has strong fitness consequences, however the mechanisms by which female birds can bias sex of their progeny in close concordance with the environment of breeding are not known. In recently established populations of house finches (Carpodacus mexicanus), breeding females lay a sex-biased sequence of eggs when ambient temperature causes early onset of incubation. We studied the mechanisms behind close association of incubation and sex-determination strategies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 60 publications
2
96
0
Order By: Relevance
“…Recent studies on birds have shown that maternal effects can be strongly sex-specific and apparently play an important role in the evolution of sexual dimorphism (Badyaev, 2005;Badyaev et al, 2005Badyaev et al, , 2006. Sex-specific maternal effects can arise by for example, mothers allocating variable amounts of nutrients or hormones to sons and daughters in relation to their own condition (Badyaev et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on birds have shown that maternal effects can be strongly sex-specific and apparently play an important role in the evolution of sexual dimorphism (Badyaev, 2005;Badyaev et al, 2005Badyaev et al, , 2006. Sex-specific maternal effects can arise by for example, mothers allocating variable amounts of nutrients or hormones to sons and daughters in relation to their own condition (Badyaev et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most of the information on oocyte proliferation and maturation and follicular steroid production comes from poultry, selected for maximal egg production; therefore, we cannot necessarily assume that the processes are exactly the same in wild birds, and some evidence exists that this is not the case (Young & Badyaev 2004;Badyaev et al 2005). Nevertheless, these studies reveal general principles of how ovarian steroids might accumulate in oocytes and how to study these processes.…”
Section: Potential Mechanisms (A) How Do Steroids Accumulate In Eggs?mentioning
confidence: 99%
“…Finally, some studies measured hormone concentrations after completion of laying (onset of incubation), which is inappropriate since gonadal androgens and oestrogen rapidly decline during that phase (e.g. Schwabl 1996a; Sockman & Schwabl 1999;Badyaev et al 2005).…”
Section: Glucocorticoids and Thyroid Hormonesmentioning
confidence: 99%
See 2 more Smart Citations